1992
DOI: 10.1083/jcb.117.4.775
|View full text |Cite
|
Sign up to set email alerts
|

High level expression of transfected beta- and gamma-actin genes differentially impacts on myoblast cytoarchitecture

Abstract: Abstract. The impact of the human/3-and 7-actin genes on myoblast cytoarchitecture was examined by their stable transfection into mouse C2 myoblasts. Transfectant C2 clones expressing high levels of human/~-actin displayed increases in cell surface area. In contrast, C2 clones with high levels of human 3,-actin expression showed decreases in cell surface area. The changes in cell morphology were accompanied by changes in actin stress-fiber organization. The/3-actin transfectants displayed well-defined filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
115
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 44 publications
9
115
0
Order By: Relevance
“…This is entirely consistent with previous studies that have shown that Tm isoforms differ in their ability to restore cell shape to transformed cells (Gimona et al, 1996) and in their impact on neuroepithelial cells (Bryce et al, 2003; Figure 6). In addition, the original demonstration that ␤ and ␥-actin carry different structural information (Schevzov et al, 1992) may be accounted for by their differential impact on Tm isoform levels and organization (Schevzov et al, 1993). In all cases, the alterations in cell shape are consistent with changes in the organization of actin filaments.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…This is entirely consistent with previous studies that have shown that Tm isoforms differ in their ability to restore cell shape to transformed cells (Gimona et al, 1996) and in their impact on neuroepithelial cells (Bryce et al, 2003; Figure 6). In addition, the original demonstration that ␤ and ␥-actin carry different structural information (Schevzov et al, 1992) may be accounted for by their differential impact on Tm isoform levels and organization (Schevzov et al, 1993). In all cases, the alterations in cell shape are consistent with changes in the organization of actin filaments.…”
mentioning
confidence: 69%
“…Previous studies that have manipulated actin and tropomyosin isoform expression in myogenic and neuroepithelial cells have led to global changes in cell dimension (Schevzov et al, 1992;von Arx et al, 1995;Mounier et al, 1997;Bryce et al, 2003). In each case, the manipulated gene products have altered the organization of actin filaments throughout the cell.…”
Section: Qualitative and Quantitative Impact Of Tropomyosin On Neuronmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the wound healing process in endothelial cells showed that the ,B-actin isoform, together with its mRNA, was exclusively distributed in leading lamellae, membrane ruffles, and advancing pseudopods (Hoock et al, 1991). Functional diversity of ,B-actin and y-actin isoforms was demonstrated in C2 myoblasts where overexpression of the human f3-actin isoform gene induced an increase in cell surface area and loss of stress fibers, whereas overexpression of the y-actin isoform was associated with a decreased surface area (Schevzov et al, 1992). To verify the role of ,B-actin in generating an enlarged cell phenotype, these authors further demonstrated that transfection of C2 myoblasts with mutant ,3-actin caused the disruption of the actin microfilament network and a decrease in membrane surface area similar to that of C2 cells that were transfected with wild-type y-actin.…”
Section: Discussionmentioning
confidence: 98%
“…Vertebrate cytoplasmic actins and muscle actins are divergent from each other by about 5% in amino acid sequence and 500 million years in time, and they have only a few charged residue interchanges located at their amino terminal ends (Meagher and Williamson, 1994). In addition, some functional differences have been demonstrated between muscle and cytoplasmic actin isovariants, and even between isovariants of cytoplasmic actins (Rubenstein, 1990;Schevzov et aL, 1992). Thus, based on the relatively extreme divergence of ACT2/ACT8 actins from other Arabidopsis actins and the preservation of many of the actin subclasses over long evolutionary periods (McDowell et al, 1996b), we propose that the ACT2/ACT8 protein subclass will show functional differences from the other Arabidopsis actin subclasses.…”
Section: Discussionmentioning
confidence: 99%